Exogenous spraying of plant’s resistance inducers improves yield and sugarcane quality - Viana, Ronaldo da Silva [UNESP]; Moreira, Bruno Rafael de Almeida [UNESP]; Lisboa, Lucas Aparecido Manzani [UNESP]; de Figueiredo, Paulo Alexandre Monteiro [UNESP]; Ramos, Sérgio Bispo [UNESP]; Ramos, Samuel Bispo [UNESP]; Dias, Gustavo Henrique de Oliveira; Moreira, Leticia Cunha; Spotoni, Mariana Teixeira; Recco, Camila Regina Silva Baleroni (My University, 2019)
Sugarcane crop is important to sugar-energy industry. Thus, the aim of this study was to evaluate yield and technological quality of Sugarcane juice obtained from the SP81-3250 variety following exogenous spraying of resistance inducers. The experiment consisted of a randomized block design with four replicates per treatment: salicylic acid (0, 5, 10, 20, and 40 μM) and acibenzolar-S-methyl (0, 0.2, 0.4, 0.8 and 1.6 g 100 L-1). The resistance inducers were sprayed using CO2-pressurized sprayer. Sugarcane tillage was harvested thirty-days after the spraying of resistance inducers and stalks were milled for juice samples extraction, in which were evaluated the following parameters: °Brix, Pol, purity, reducing sugars (RS), total reducing sugars (TRS), theoretical sugar recoverable (TSR), fibres and yields of sugar and stalks. Obtained data was submitted to following statistical tests (P < 0.05): Shapiro-Wilk’s normality, Fisher’s variance, regression, and Pearson’s linear correlation. Results showed that quadratic trends rejected null hypothesis for almost all parameters. Salicylic acid levels till 10 μM increased °Brix, Pol, purity, TRS, TSR contents and sugar and stalks yield. However, 20 and 40 μM showed negative effects on juice technological quality and agronomic performance. Therefore, the elicitors improved photosynthetic characteristics and sugarcane physiological maturation. It was concluded that salicylic acid and acibenzolar-S-methyl levels till 10 μM and 0.8 g 100 L-1, respectively, are recommendable to management of SP81-3250 variety.
Keywords: Acibenzolar-S-methyl; Inducers; Phytohormones; Plant resistance; Saccharum spp; Salicylic acid